Complex evaluation of calendula officinalis flowers by main biologically active substances content - E. L. Malankina; L. N. Kozlovskaya; L. V. Biktimyrova; E. L. Komarova (Овощи России)
Relevance. The demand for medicinal raw materials of Calendula officinalis L. is determined by the high content of pharmacologically significant compounds. Comparison of the most common ornamental cultivars of Calendula officinalis L.) in terms of yield and content of biologically active substances in the raw material helps to identify the most promising cultivars in terms of a set of indicators.Materials and methods.The decorative cultivars Apricot, Art Shads, Fiesta Gitana, Kabluna golden-yellow, Orange King, Orange Balls, Yellow Gitana and Golden Balls, characterized by large inflorescences and terry, were used as prototypes. The cultivar Kalta, widely used for the production of medicinal raw materials, was chosen as a control. The experiments were laid on the experimental plots of the Fruit Growing Laboratory of the Russian State Agricultural University – Moscow Timiryazev Agricultural Academy. Productivity was determined as the total weight of inflorescences harvested during the entire season per unit area. The amount of flavonoids was determined by spectrophotometry. The amount of polysaccharides was determined according to the modified Draywood method. The lutein content was determined by HPLC.Results.To obtain inflorescences we can recommend to use the variety Orange King, which, with a satisfactory yield (0.363 kg/m2), was characterized by a high content of flavonoids (1.2%) and satisfactory (35.9%) extractives and corresponds to the quality of raw materials required by GF XIV. In addition, this variety was characterized by an increased content of polysaccharides (20.3%). The Varieties Apricot and Yellow Gitana were characterized by high productivity (562±49 and 507±41 g/m2, respectively). Their raw materials can be used by production of herbal teas, where the content of flavonoids is not regulated. As sources of lutein, one should pay attention to the ligulate flowers of the varieties Apricot, Fiesta Gitana, Golden balls. In the variety Kabluna, with the maximum lutein content, the proportion of reed flowers in the inflorescence was only 38%. In varieties with large inflorescences, the content of lutein in reed flowers was higher (R=0.685). Large non-double inflorescences will be most productive in this indicator.